Redefining Standard Model Cosmology - Albert Robson, Brian (IntechOpen, 2019)
The current standard model of cosmology is based primarily on two incompatible theoretical models: (1) the standard model of particle physics, which describes the physics of the very small in terms of quantum mechanics, and (2) the general theory of relativity, which describes the physics of the very large in terms of classical physics. Both these theoretical models are considered to be incomplete in the sense that they do not provide any understanding of several empirical observations, such as the Big Bang, dark matter, dark energy, gravity, and matter-antimatter asymmetry in the universe. The main aim of this book is to discuss these serious problems that threaten to undermine the current standard model of cosmology.